2010
DOI: 10.1007/s12310-010-9045-2
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility, Assessment, and Educational Placement Issues for Students Classified with Emotional Disturbance: Federal and State-Level Analyses

Abstract: The purpose of this paper is to contribute to an understanding of how state education authorities conceptualize and utilize the construct of emotional disturbance (ED) within the special education system. Specifically, this study examined variability across state definitions of ED and the extent to which such differences in definition are associated with ED identification and educational placement rates. Relevant literature and publicly disseminated documentation at the federal and state levels were reviewed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 26 publications
1
21
1
Order By: Relevance
“…Beyond the problems inherent in the social maladjustment clause, several other serious concerns and deficiencies associated with the federal definition are evident, and these have been enumerated and discussed in detail over the years since Pub. L. 94–142 was enacted (Becker et al, ; Clarizio, ; Forness & Kavale, ; Hanchon & Allen, in press; Merrell & Walker, ; Skiba & Grizzle, ). The major criticisms have focused on the lack of empirical support for the eligibility criteria; the vague, ambiguous, and outdated language included in the definition; and the failure to successfully lobby for changes to the law.…”
mentioning
confidence: 99%
“…Beyond the problems inherent in the social maladjustment clause, several other serious concerns and deficiencies associated with the federal definition are evident, and these have been enumerated and discussed in detail over the years since Pub. L. 94–142 was enacted (Becker et al, ; Clarizio, ; Forness & Kavale, ; Hanchon & Allen, in press; Merrell & Walker, ; Skiba & Grizzle, ). The major criticisms have focused on the lack of empirical support for the eligibility criteria; the vague, ambiguous, and outdated language included in the definition; and the failure to successfully lobby for changes to the law.…”
mentioning
confidence: 99%
“…Given the vagaries of the language contained in the federal law, which is similar to most states’ definitions (Becker et al., ), identifying students who rightfully qualify to receive special education services under the ED category is an arduous endeavor, to the extent that Knitzer () referred to these vulnerable students as America's ‘unclaimed children.’ Although the decision of whether to classify a child as ED is ultimately made by the multidisciplinary team, typically the brunt of the identification process falls upon the shoulders of the school psychologist. Given this context, an important and germane question to ask is “How are school psychologists translating the federal guidelines into practice as they identify students under the ED category?”…”
mentioning
confidence: 99%
“…The Department of Education (DOE) did not define SM, leaving it up to states and local educational authorities to decide which behaviors, emotions, or mental states constitute SM, and even whether to include the SM exclusion. Prior researchers have attempted to describe and quantify the variability among state definitions of ED (Becker et al, 2011;Olympia et al, 2004;Skiba, Grizzle, & Minke, 1994), but none of them identified by citation the laws or regulations supporting their conclusions.…”
Section: Statutory and Regulatory Backgroundmentioning
confidence: 99%
“…As we attempt to distinguish SM and ED, it is important to remember that special education categories represent administrative labels, not diagnoses, determined by education policy (Becker et al, 2011). A student with ED does not necessarily have a mental disorder as defined in the psychiatric nosology.…”
Section: Policy Debatementioning
confidence: 99%
See 1 more Smart Citation